2016
DOI: 10.1038/srep38206
|View full text |Cite
|
Sign up to set email alerts
|

Three millennia of heavy rainfalls in Western Mediterranean: frequency, seasonality and atmospheric drivers

Abstract: Documenting subdecadal-scale heavy rainfall (HR) variability over several millennia can rarely be accomplished due to the paucity of high resolution, homogeneous and continuous proxy records. Here, using a unique, seasonally resolved lake record from southern Europe, we quantify temporal changes in extreme HR events for the last 2,800 years in this region and their correlation with negative phases of the Mediterranean Oscillation (MO). Notably, scarce HR dominated by a persistent positive MO mode characterizes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
80
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(95 citation statements)
references
References 55 publications
(74 reference statements)
3
80
0
2
Order By: Relevance
“…Our results are in agreement with other palaeohydrological studies in the area for the same period (Benito et al, 2010;Machado et al, 2011) highlighting a tendency from many regions to increase the frequency of large floods and extreme hydro-meteorological events during transition periods of rapid climate change (Knox, 2000;Macklin et al, 2006). During the onset and termini of the Medieval Warm Period and in some decades of the Little Ice Age, major flooding increased their frequency in the western Mediterranean (Benito et al, 2015a;Corella et al, 2016). During the wetter phases of late 19 th century, major flooding occurred in all seasons, while in the second half of the twentieth century, from AD 1945 to AD 1973, more than 70% of extreme floods are linked to autumn rain patterns with high inter-annual variability (Benito et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…Our results are in agreement with other palaeohydrological studies in the area for the same period (Benito et al, 2010;Machado et al, 2011) highlighting a tendency from many regions to increase the frequency of large floods and extreme hydro-meteorological events during transition periods of rapid climate change (Knox, 2000;Macklin et al, 2006). During the onset and termini of the Medieval Warm Period and in some decades of the Little Ice Age, major flooding increased their frequency in the western Mediterranean (Benito et al, 2015a;Corella et al, 2016). During the wetter phases of late 19 th century, major flooding occurred in all seasons, while in the second half of the twentieth century, from AD 1945 to AD 1973, more than 70% of extreme floods are linked to autumn rain patterns with high inter-annual variability (Benito et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…(, ) identified a pulse of storm‐related aeolian activity in the neighbouring coast of Portugal at 1·2 ka cal bp , corresponding to the Rapid Climate Change event of 1·0 to 1·2 ka cal bp (Mayewski et al ., ). Increased storm activity has also been detected in the coastal sedimentary archives of the English Channel and Brittany (north‐west France) (Sorrel et al ., ; Van Vliet‐Lanoë et al ., ,b) and in the lacustrine records of the Mediterranean Iberian region (Corella et al ., ; Sánchez‐López et al ., ) at this time interval, which roughly corresponds to the Dark Ages Cold Event (DA)/Medieval Climatic Anomaly (MCA) transition. A combination of high tides and storm surges in the north‐east Atlantic under this favourable palaeoclimatic situation could explain the breaching of the outlet channel and the catastrophic erosive event in Doniños.…”
Section: Discussionmentioning
confidence: 99%
“…Costas et al (2012Costas et al ( , 2016 identified a pulse of storm-related aeolian activity in the neighbouring coast of Portugal at 1Á2 ka cal BP, corresponding to the Rapid Climate Change event of 1Á0 to 1Á2 ka cal BP (Mayewski et al, 2004). Increased storm activity has also been detected in the coastal sedimentary archives of the English Channel and Brittany (north-west France) Van Vliet-Lano€ e et al, 2014a,b) and in the lacustrine records of the Mediterranean Iberian region (Corella et al, 2016;S anchez-L opez et al, 2016) (2015). Black circles correspond to control age samples.…”
Section: Long-term Low-frequency Patterns Of Environmental Change In mentioning
confidence: 95%
“…Changes in the frequency of severe weather events determine the occurrence of damaging hydrological events (Diodato et al, 2019;Petrucci et al, 2019), which in turn affect many natural and human systems (Corella et al, 2016;Sofia et al, 2017). Modeling rainfall intensity can help to quantifying the effect of these extreme phenomena that involve complex landscape and ecosystem scenarios within multiple event feedback forms (e.g., Thomas, 2001;Mulligan and Wainwright, 2013;Harris et al, 2018).…”
Section: Introductionmentioning
confidence: 99%